Streptococcus pneumoniae and Influenza A Virus Co-Infection Induces Altered Polyubiquitination in A549 Cells - Sura, Thomas; Gering, Vanessa; Cammann, Clemens; Hammerschmidt, Sven; Maaß, Sandra; Seifert, Ulrike; Becher, Dörte (Frontiers in Cellular and Infection Microbiology, 2022)
Epithelial cells are an important line of defense within the lung. Disruption of the epithelial barrier by pathogens enables the systemic dissemination of bacteria or viruses within the host leading to severe diseases with fatal outcomes. Thus, the lung epithelium can be damaged by seasonal and pandemic influenza A viruses. Influenza A virus infection induced dysregulation of the immune system is beneficial for the dissemination of bacteria to the lower respiratory tract, causing bacterial and viral co-infection. Host cells regulate protein homeostasis and the response to different perturbances, for instance provoked by infections, by post translational modification of proteins. Aside from protein phosphorylation, ubiquitination of proteins is an essential regulatory tool in virtually every cellular process such as protein homeostasis, host immune response, cell morphology, and in clearing of cytosolic pathogens. Here, we analyzed the proteome and ubiquitinome of A549 alveolar lung epithelial cells in response to infection by either Streptococcus pneumoniae D39Δcps or influenza A virus H1N1 as well as bacterial and viral co-infection. Pneumococcal infection induced alterations in the ubiquitination of proteins involved in the organization of the actin cytoskeleton and Rho GTPases, but had minor effects on the abundance of host proteins. H1N1 infection results in an anti-viral state of A549 cells. Finally, co-infection resembled the imprints of both infecting pathogens with a minor increase in the observed alterations in protein and ubiquitination abundance.